2022
DOI: 10.11591/ijphs.v11i4.21529
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction among primary health care nurses

Abstract: This study aimed to analyze the job satisfaction of nurses in primary health care facilities. This study employed a quantitative descriptive design. The research used a cross-sectional approach. This study involved 226 nurses who worked in 15 inpatients primary health care. The sampling technique uses a proportionate simple random sampling technique. Nurse job satisfaction instruments assessed context factors and content factors. Nurse job satisfaction on context factor was in a good category by a big responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…This low caring behaviour of nurses can be influenced by several factors, both internal and external. 35 The low level of caring behaviour in nurses can be influenced by various factors. Research has shown that nurses' caring behaviour may be influenced by burnout, which can result from the emotional demands of providing care.…”
Section: Discussionmentioning
confidence: 99%
“…This low caring behaviour of nurses can be influenced by several factors, both internal and external. 35 The low level of caring behaviour in nurses can be influenced by various factors. Research has shown that nurses' caring behaviour may be influenced by burnout, which can result from the emotional demands of providing care.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as work atmosphere, interpersonal relationships, workload, stress, training, and autonomy were identified as influential within the work environment [10]. It was found that nurses who experience positive job satisfaction are less likely to resign from their positions [11].…”
Section: Discussionmentioning
confidence: 99%
“…A negative work atmosphere increases workplace dissatisfaction, which can boost the frequency of resignation. Nurses who operate in a supportive environment with positive job satisfaction are less likely to quit their jobs than those who do not [11].…”
Section: Impact Of Work Environment On Job Resignationmentioning
confidence: 99%
See 1 more Smart Citation
“…Esto, se ve garantizado por la SL de las enfermeras en los indicadores de responsabilidad, logros, reconocimiento del desempeño que no ha alcanzado el 60%. Por consiguiente, la SL del personal de enfermería en atención primaria es positiva, sin embargo, todavía requiere potencializar el factor de contenido (Soesanto et al, 2022).…”
Section: Satisfacción Laboral (Sl)unclassified